2010
DOI: 10.1029/2009jc005578
|View full text |Cite
|
Sign up to set email alerts
|

Momentum balances on the inner continental shelf at Martha's Vineyard Coastal Observatory

Abstract: [1] The subtidal, depth-average momentum balances in 12 m and 27 m water depth are investigated using observations from 2001 to 2007 of water velocity, temperature, and density; bottom pressure; surface gravity waves; and wind stress. In the fluctuating across-shelf momentum budget, the dominant terms are surface wind stress, pressure gradient, and Coriolis acceleration. The balance is a combination of (1) the geostrophic balance expected at midshelf sites and (2) the coastal setup and setdown balance driven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 50 publications
12
58
1
Order By: Relevance
“…The Coriolis force and the radiation stress played secondary roles in the momentum balance. In particular, the radiation stresses were 1 order of magnitude smaller than the dominant acceleration, pressure gradient and frictional terms, consistent with other studies that ignored wave forcing outside the surf zone (Lentz et al, 1999;Fewings and Lentz, 2010). In a region 150 km north of our study area, in water depths of 28 m off the Tet River, Michaud et al (2012) confirmed numerically that the wave effects on the inner-shelf circulation are relatively small even during a storm event.…”
Section: Momentum Evolution In the Inner Shelfsupporting
confidence: 75%
See 2 more Smart Citations
“…The Coriolis force and the radiation stress played secondary roles in the momentum balance. In particular, the radiation stresses were 1 order of magnitude smaller than the dominant acceleration, pressure gradient and frictional terms, consistent with other studies that ignored wave forcing outside the surf zone (Lentz et al, 1999;Fewings and Lentz, 2010). In a region 150 km north of our study area, in water depths of 28 m off the Tet River, Michaud et al (2012) confirmed numerically that the wave effects on the inner-shelf circulation are relatively small even during a storm event.…”
Section: Momentum Evolution In the Inner Shelfsupporting
confidence: 75%
“…The PGFR includes a contribution by a direct response to the local wind forcing (for instance during 13 March), which is not immediately obvious in PGFO. During the wind peaks, the positive pressure-gradient force partially counterbalanced the wind stress in a manner consistent with other observational studies (Lee et al, 1984;Lentz, 1994;Fewings and Lentz, 2010). Despite its potentially large uncertainty, we use PGFR in the analysis of the momentum balance evolution because it is consistent with the estimates for the other momentum terms.…”
Section: Momentum Balance In the Inner Shelfmentioning
confidence: 65%
See 1 more Smart Citation
“…Studies over different inner-shelves (Lentz et al, 1999;Liu and Weisberg, 2005;Fewings and Lentz, 2010) seem to agree that the circulation is mainly forced by along-shelf pressure gradient (generated by local wind forcing) and wind stress, though other processes can also be important depending on water depth and wave regime.…”
Section: Discussionmentioning
confidence: 97%
“…The inner shelf is defined as the region offshore of the surf zone where surface and bottom boundary layers overlap (Lentz 1995). The dynamics in this region are dominated by the forcing of alongshore wind stress and alongshore pressure gradients, balanced by bottom stress response (Pettigrew 1980, Lentz and Winant 1986, Lentz 1994, Liu and Weisberg 2005, Gutierrez et al 2006, Fewings and Lentz 2010, Lentz and Fewings 2012. Coastal and bathymetric variations modify inner shelf circulation and the momentum balance (Dragos and Aubrey 1990, Yankovsky and Garvine 1998, van de Meene and van Rijn 2000a, Kirincich and Barth 2009, Kumar et al 2013).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%